Decoding IELTS writing performance: Grammatical Clauses mastery by Universitas Ahmad Dahlan students - Pratama, Muhammad Adi; Munandar, Aris (NOTION: Journal of Linguistics, Literature, and Culture, 2024)
Indonesian learners of English produced ungrammaticalities in their writing for the International English Language Testing System (IELTS) and faced complicated writing score descriptors for self-evaluations and improvements. These problems were observed among students at Universitas Ahmad Dahlan during their preparatory course for IELT. To address this issue, this study focused on identifying some rules in grammar, the grammatical and ungrammatical clauses based on subject-verb (S + V) structures in their writing performances and measuring the proportions of the two clause types in accordance with the performance’s score variation. Both qualitative and quantitative methods were employed. To do so, the study conducted archival research by retrieving data from the teacher’s course documents. The archived handwritten writing performances were transcribed manually into digital texts. It employed syntactic analysis to classify the clauses as either grammatical or ungrammatical. It converted the numbers of each clause type per performance into percentages for comparison, and grouped them according to the different scores as the variable. The results showed that the participants produced predominantly simple grammatical clauses to minimize failures when generating more complex structures. To achieve the minimum score of 6 in the writing section, the proportion of grammatically correct and incorrect clauses should be above 47% and below 53%, respectively. These findings offer valuable insights into predicting scores, especially concerning the dimension of ’grammatical range and accuracy in the writing assessment, which benefit both learners and educators.